THE MODEL OF EDUCATION SANDBOX ADMINISTRATION BASED ON SAPPURISADHAMMA PRINCIPLES OF PRIMARY SCHOOLS UNDER SAMUTPRAKAN PRIMARY EDUCATIONAL SERVICE AREA OFFICE - Angkurasi, Muthita; Chaisuk, Peravat; Kaewtongyai, Yudthawee (Journal of Educational Review Faculty of Education in MCU, 2024)
This research article aimed: 1) to study the needs of educational innovation area management in primary schools, 2) to develop a model of educational innovation area management based on the principle of Sappurisadhamma of primary schools, and 3) to evaluate the model of educational innovation area management based on the principle of Sappurisadhamma of primary schools. This research was a mixed-method research with 3 research steps: Step 1: quantitative research using a questionnaire with a sample of 258 administrators and teachers; Step 2: qualitative research using interviews with 11 key informants and focus group discussions with 9 experts; and Step 3: quantitative research using a format evaluation form with a sample of 90 people. The results of the research found that 1) the needs of educational innovation area management in primary schools had values of 5 needs, ranked from highest to lowest, as following: methods, concepts, teaching media, management, and processes, respectively; 2) The model of educational innovation area management based on the principle of Sappurisadhamma of primary schools under the Office of the Samut Prakan Primary Educational Service Area consisting of 5 main components: (1) principles, (2) objectives, (3) integration, which were divided into 5 aspects: concepts, methods, processes, teaching media and management, (4) application, (5) evaluation of the use of the model and 3) evaluation of the model of the administration of educational innovation areas of primary schools, overall, the evaluation results were at the highest level. When considering each aspect, the evaluation results were at the highest level in all 4 aspects: usefulness, correctness, appropriateness, and feasibility. This indicated that the developed model was appropriate, correct, feasible to practice, and could be utilized. It could be summarized as knowledge from the research “EMS”.